А) + у =1 , умножаем всё уравнение на 8, то 5+8у=8 8у=8-5 8у=3 у= б) 1-у=, умножаем всё уравнение на 12, то 12 - 12у= 7 -12у=7-12 -12у=-5 у= -5/(-12) у= в) у+=1, умножаем всё уравнение на 16, то 16у+5=16 16у=16-5 16у=11 у= г) 1-у=, умножаем всё уравнение на 24, то 24 - 24у =5 -24у=5-24 -24у=-19 у=
5+8у=8
8у=8-5
8у=3
у=
б) 1-у=, умножаем всё уравнение на 12, то
12 - 12у= 7
-12у=7-12
-12у=-5
у= -5/(-12)
у=
в) у+=1, умножаем всё уравнение на 16, то
16у+5=16
16у=16-5
16у=11
у=
г) 1-у=, умножаем всё уравнение на 24, то
24 - 24у =5
-24у=5-24
-24у=-19
у=